A Review of Haptoglobin Typing Methods for Disease Association Study and Preventing Anaphylactic Transfusion Reaction. (21st February 2013) - Ko, Dae-Hyun; Chang, Ho Eun; Kim, Taek Soo; Song, Eun Young; Park, Kyoung Un; Song, Junghan; Han, Kyou Sup
Abstract : Haptoglobin, the product of the H p gene, is a glycoprotein involved in the scavenging of free hemoglobin. Haptoglobin levels increase or decrease in response to various acquired conditions, and they are also influenced by genetic predisposition. There were 2 major alleles, H p 1 and H p 2, and 1 minor allele, H p d e l . Many researchers have attempted to study the haptoglobin types and their association with disease; however, no definitive conclusions have been reached yet. It is reported that patients who are genetically deficient in haptoglobin are at risk of anaphylaxis against blood components containing haptoglobin. Haptoglobin genotypes also affect the reference intervals of haptoglobin levels. Many studies have attempted to establish simple and accurate typing methods. In this paper, we have broadly reviewed several methods for haptoglobin typing—phenotyping, Southern blotting, conventional PCR, real-time PCR, and loop-mediated isothermal amplification. We discuss their characteristics, clinical applications, and limitations. The phenotyping methods are time consuming and labor intensive and not designed to detect patients harboring H p d e l . The rapid and robust haptoglobin genotyping may help in preventing fatal anaphylactic reactions and in establishing the relationships between the haptoglobin phenotypes and diseases.